Expert report on the Elina Sushkevich case - G. C. Di Renzo (Акушерство, гинекология и репродукция, 2020)
Per request of MD, Dr Sci Med, Professor, Academician of RAS Nikolay N. Volodin, President of Russian association of specialists in perinatal medicine (RASPM) one of leading specialists in obstetrics, gynecology and perinatal medicine in the world prof. Gian Carlo Di Renzo have prepared the Expert Report on the Elina Sushkevich case. Taken into account the importance of this case for healthcare professionals, we publish the full text in the original and translated into Russian.